Generation of a recombinant Saffold Virus expressing UnaG as a marker for the visualization of viral infection - Okuwa, Takako; Himeda, Toshiki; Utani, Koichi; Higuchi, Masaya (Virology journal, 2023)
Background Saffold virus (SAFV), which belongs to the genus Cardiovirus of the family Picornaviridae , is associated with acute respiratory or gastrointestinal illnesses in children; it is also suspected to cause severe diseases, such as acute flaccid paralysis and aseptic meningitis. However, the understanding of the mechanism of its pathogenicity is still limited due to the many unknowns about its lifecycle; for example, the cellular receptor for its infection remains to be determined. A system to monitor SAFV infection in vitro and in vivo is required in order to accelerate research on SAFV. Results We generated a recombinant SAFV expressing green fluorescent protein (GFP) or UnaG, a novel fluorescent protein derived from Japanese eel. HeLa cells infected by either GFP or UnaG-expressing SAFV showed a bright green fluorescent signal, enabling convenient monitoring of SAFV infection. However, the expression of GFP but not UnaG was quickly lost during virus passaging due to the difference in genetic stability in the SAFV virus genome; the UnaG gene was stably maintained in the virus genome after at least five passages. Conclusions SAFV infection of cultured cells can easily be monitored using UnaG-expressing SAFV, which is superior to GFP in terms of genetic stability in the virus genome. This virus could be a useful tool for SAFV research, such as comparing the susceptibility of various cells to SAFV infection and evaluating the effects of antivirals on SAFV infection in high-throughput screening.